Characterisation of interfacial adhesion in hemp composites after H2O2 and non-thermal plasma treatments. (October 2021) - Barbière, Romain; Touchard, Fabienne; Chocinski-Arnault, Laurence; Fourré, Elodie; Leroy, Eric; Barrault, Joël
Interface optimisation for continuous hemp reinforcements in epoxy resin is a current challenge for the development of biocomposites. A chemical treatment based on hydrogen peroxide and a physical one using a non-thermal plasma have been tested to optimise interface adhesion, by varying several parameters. FTIR analysis and FE-SEM observations have shown the effects of the treatments on chemical and morphological aspects of the treated yarns. Tensile tests on hemp yarns have allowed the selection of the treatment parameters leading to the best strength. Fragmentation tests results showed that the two treatments lead to a decrease in the fragment lengths and thus, an enhancement of the Interfacial Shear Strength (IFSS) values in comparison with the untreated yarn. This is confirmed by the micro-CT observations of the debonding lengths in the vicinity of each yarn fragment extremity. Finally, the plasma treated samples exhibit a better interface adhesion quality (IFSS = 44.7 ± 4 MPa) than the chemically treated ones (IFSS = 24.2 ± 4 MPa), which are better than the non-treated ones (IFSS = 13.5 ± 4 MPa).